RESEARCH OF OBJECTIVE FUNCTION IN PARAMETRIC IDENTIFICATION TASKS FOR INTERVAL DIFFERENCE OPERATOR WITH REQUIRED ACCURACY - Dyvak, Mykola; Dyvak, Taras; Stakhiv, Petro (International Journal of Computing, 2011)
The paper presents the problems of parametric identification of nonlinear difference operator based on interval data. It is showed that, formally, this problem belongs to the task of finding at least of one solution of interval system of nonlinear algebraic equations. It is proposed and justified the use of the methods of random search with a nonlinear discrete criterion function for solving this task. The properties of the function are researched in this paper.